Respostas
respondido por:
3
a15 = ?
a1 = 15
r = -5
n = 15
an = a1 + (n - 1)r
a15 = 15 + (15 - 1)*(-5)
a15 = 15 + (14)(-5)
a15 = 15 - 70
a15 = -55
a1 = 15
r = -5
n = 15
an = a1 + (n - 1)r
a15 = 15 + (15 - 1)*(-5)
a15 = 15 + (14)(-5)
a15 = 15 - 70
a15 = -55
respondido por:
2
a1 = 15
a2 = 10
r = a2 - a1 = 10 - 15
r = - 5
n = 15
a15 = ?
an = a1 + (n - 1).r
a15 = a1 + (15 - 1).r
a15 = a1 + 14r
a15 = 15 + 14.(- 5)
a15 = 15 - 70
a15 = - 55
a2 = 10
r = a2 - a1 = 10 - 15
r = - 5
n = 15
a15 = ?
an = a1 + (n - 1).r
a15 = a1 + (15 - 1).r
a15 = a1 + 14r
a15 = 15 + 14.(- 5)
a15 = 15 - 70
a15 = - 55
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás